The rules of programming how to write better code - Zimmerman, Chris (Ascent Audio, 2023)
This philosophy-of-programming guide presents a unique and entertaining take on how to think about programming. A collection of twenty-one pragmatic rules, each presented in a stand-alone chapter, captures the essential wisdom that every freshly minted programmer needs to know and provides thought-provoking insights for more seasoned programmers. Author Chris Zimmerman, cofounder of the video game studio Sucker Punch Productions, teaches basic truths of programming by wrapping them in memorable aphorisms and driving them home with examples drawn from real code. This practical guide also helps managers looking for ways to train new team members. The rules in this book include: As simple as possible, but no simpler; Let your code tell its own story; Localize complexity; Generalization takes three examples; Work backward from your result, not forward from your code; The first lesson of optimization is don't optimize; A good name is the best documentation; Bugs are contagious; Eliminate failure cases; Code that isn't running doesn't work; and Sometimes you just need to hammer the nails.